Comparative Study of Physicochemical Characteristics of Broiler Chicken Manure under Different Housing Management Systems in East Kalimantan, Indonesia - Ali Sadikin; Rusmini; La Mudi; Zainal Abidin; Daryono (JURNAL AGRIMENT, 2026)
Broiler chicken manure is widely utilized as an organic amendment to improve soil fertility and support sustainable agriculture. Its physicochemical characteristics may vary depending on housing management systems and bedding materials used during production. This study aimed to compare the physicochemical characteristics of broiler chicken manure obtained from three different management systems in Kutai Kartanegara Regency, East Kalimantan, Indonesia. The analyzed samples consisted of Km 16 (rice husk litter, closed-house system), MK (pure manure without litter, open-house system), and MH (sawdust litter, open-house system). Laboratory analyses were conducted to determine pH, moisture content, organic C, total N, and C/N ratio. The results showed variations among samples, with pH ranging from 7.72–7.98, moisture content from 19.70–20.71%, organic C from 23.01–31.09%, total N from 1.707–2.237%, and C/N ratio from 11.118–18.210. The Km 16 sample tended to have higher organic C content, while the MK sample showed relatively higher nitrogen content. All samples exhibited C/N ratios below 20, indicating relatively mature organic fertilizer suitable for agricultural application. These findings suggest that litter materials and housing management systems may contribute to differences in manure characteristics and their potential utilization for sustainable agriculture and post-mining land rehabilitation.